Evaluasi Kebijakan Bantuan Keuangan Khusus tentang Bali Smart Island di Desa Pakraman di Kecamatan Buleleng - Widiasa, Ketut; Widnyani , Ida Ayu Putu Sri; Astawa , I Wayan (Penerbit Goodwood, 2023)
Purpose: The Special Financial Assistance (BKK) policy from the Province of Bali through the Bali Smart Island (BSI) program in Pakraman Village in Buleleng Subdistrict is to improve digital-based public services by providing free wifi.With equitable access to information technology such as the internet network in Pakraman Village, it can realize equitable development in all fields. Research methodology: This research method uses a qualitative descriptive approach. Results: This research method uses a qualitative descriptive approach. The results of the research show that the BSI BKK Policy Evaluation for Pakraman Village in Buleleng District with a 4-indicator approach, namely input, process, output and outcomes, has not been optimal. Limitations: In this study only used a few informants, therefore future research may consider using more informants. Contribution: This research contributes to the Regional Government of Buleleng Regency.